Characterization of sympathicotonia in post‐covid condition (long covid) and healthy controls using long‐term electrodermal activity (EDA) follow‐up - Mustonen, Timo; Kytölä, Pasi; Lantto, Hanna; Lager, Erika; Vangelova‐Korpinen, Velina; Virrantaus, Hélène; Sulg, Aleksandra; Stålnacke, Sanna; Posharina, Tatiana; Luukkonen, Ritva; Uusitalo, Arja; Piirilä, Päivi; et al. (Wiley, 2026)
Purpose
After SARS-CoV-2 infection, some patients develop post-COVID condition (PCC), often associated with sympathicotonia. This study aimed to characterize sympathicotonia in PCC patients using a novel long-term electrodermal activity (EDA) analysis via a smart ring and evaluate its clinical applicability.
Methods
Seventeen PCC patients were recruited from a Long Covid outpatient clinic, and 18 healthy controls volunteered. PCC patients were divided based on self-reported symptoms into those with or without sympathicotonia. A 14-day EDA monitoring was conducted. Sympathetic nervous system (SNS) activity was expressed as a double normalized index of electrodermal activity (DNE), with higher levels indicating higher SNS activity. Orthostatic tests were performed to identify orthostatic sympathicotonia. DNE levels, representing EDA, were compared to self-reported and orthostatic sympathicotonia.
Results
DNE levels did not differ between PCC patients with (N = 12) or without (N = 5) self-reported sympathicotonia or compared with nonsympathetic controls. When dividing all participants by orthostatic test results, DNE levels were lower during day (08:00–14:00; p < 0.05) but higher during late night (00:00–02:00; p < 0.05) in those with orthostatic sympathicotonia (N = 21) compared to those without (N = 14), with the 24-h comparison significant (p = 0.022). Among PCC patients, DNE levels were higher in orthostatic nonsympathicotonic (N = 7) than orthostatic sympathicotonic (N = 10) during morning (09:00–12:00; p < 0.05), with the 24-h comparison significant (p = 0.044).
Conclusion
Self-reported symptoms did not distinguish sympathicotonia. However, individuals with orthostatic test-identified sympathicotonia had heightened EDA, indicating increased sympathetic activity, particularly during late night. PCC was not identifiable by EDA. Long-term EDA monitoring may provide an objective tool for detecting sympathicotonia independently of self-reported symptoms.